ATP and phosphocreatine utilization in single human muscle fibres during the development of maximal power output at elevated muscle temperatures - Gray, S. R.; Söderlund, K.; Ferguson, R. A. (Journal of Sports Sciences, 2008)
In this study, we examined the effect of muscle temperature (Tm) on adenosine triphosphate (ATP) and phosphocreatine utilization in single muscle fibres during the development of maximal power output in humans. Six male participants performed a 6-s maximal sprint on a friction-braked cycle ergometer under both normal (Tm = 34.3°C, s = 0.6) and elevated (Tm = 37.3°C, s = 0.2) muscle temperature conditions. During the elevated condition, muscle temperature of the legs was raised, passively, by hot water immersion followed by wrapping in electrically heated blankets. Muscle biopsies were taken from the vastus lateralis before and immediately after exercise. Freeze-dried single fibres were dissected, characterized according to myosin heavy chain composition, and analysed for ATP and phosphocreatine content. Single fibres were classified as: type I, IIA, IIAX25 (1 - 25% IIX isoform), IIAX50 (26 - 50% IIX), IIAX75 (51 - 75% IIX), or IIAX100 (76 - 100% IIX). Maximal power output and pedal rate were both greater (P < 0.05) during the elevated condition by 258 W (s = 110) and 22 rev · min-1 (s = 6), respectively. In both conditions, phosphocreatine content decreased significantly in all fibre types, with a greater decrease during the elevated condition in type IIA fibres (P < 0.01). Adenosine triphosphate content was also reduced to a greater (P < 0.01) extent in type IIA fibres during the elevated condition. The results of the present study indicate that after passive elevation of muscle temperature, there was a greater decrease in ATP and phosphocreatine content in type IIA fibres than in the normal trial, which contributed to the higher maximal power output.